الصحة والمرض وأثرهما في التنميةدراسة تحليلية للواقع الصحي في مدينة الموصل (University of Mosul-college of Basic Education, 2009)
حاول البحث التعرف إلى الواقع الصحي في مدينة الموصل للفترة المحصورة (1994-2007) وانعكاساته على عملية التنمية وقد توصل البحث الى ان الواقع الصحي يعاني من اختلالات عديدة ممثلة بوفيات الأطفال ووفيات الأمهات وهجرة الأطباء وقلة إعداد الممرضين هذا مما يؤثر سلبا على تنمية المجتمع وتقدمه .The study tried to recognize the health reality in Mosul City for the years 1994-2007 and it's reflection on the developmental process .The study reached the conclusion that the health situation suffering from many disorders .These include: high rate of children and mothers death ,migration of physicians and a decrease in the number of nurses .These factors have a negative influence on the development and progress of the community .